2020
DOI: 10.21203/rs.3.rs-48913/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A potential probiotic- Lachnospiraceae NK4A136 group: Evidence from the restoration of the dietary pattern from a high-fat diet

Abstract: Background: High-fat diet (HFD) that contributes to obesity is one of the pivotal risk factors for metabolic syndrome and cancers. The dietary pattern can shape the intestinal bacterial community and influence the physiological parameters. This study aimed to investigate whether the short-term dietary pattern shift from HFD to a balanced chow diet (CD) could correct HFD-induced colonic dysbiosis and reverse adverse health effects and identify the specific bacteria that changed by dietary patterns. Results: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…In addition, the HN6 group displayed the lowest relative abundance of Lachnospiraceae NK4A136 and the highest relative abundance of Ruminiclostridium_6. Lachnospiraceae NK4A136 is considered to be a potential probiotic and exerts anti-inflammation effects [87]. Higher Ruminiclostrid-ium_6 abundance was positively correlated with cytokine levels [88].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the HN6 group displayed the lowest relative abundance of Lachnospiraceae NK4A136 and the highest relative abundance of Ruminiclostridium_6. Lachnospiraceae NK4A136 is considered to be a potential probiotic and exerts anti-inflammation effects [87]. Higher Ruminiclostrid-ium_6 abundance was positively correlated with cytokine levels [88].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of Lachnospiraceae.NK4a136.group was significantly increased in the ileum and colon of vaccinated mice. Lachnospiraceae.NK4a136.group is a potential butyrate-producer associated with metabolic fitness and gut homeostasis [ 60 , 61 ] and probiotic activity in mice [ 62 ]. We found that Lachnospiraceae.NK4a136.group constituted ∼20% of the sequenced bacterial taxa in vaccinated mice, which makes it a strong candidate for future testing related to glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…52 Furthermore, the Lachno-spiraceae_NK4A136_group was supposed to play a probiotic role in the mouse obesity model. 53,54 Therefore, the Lachnospiraceae_NK4A136_group, the core beneficial bacteria regulated by EP, is suggested to play a crucial role in protecting mice from PM-induced lung injury. Besides, it can be observed that the genera of bacteria regulated by TI and ES were different from those regulated by EP, which may partially explain why TI (a combination of ES and EP) showed weaker protection than EP or ES, but further investigation on the interaction between microbiota modulated by ES and EP is needed to confirm this hypothesis.…”
Section: ■ Discussionmentioning
confidence: 99%